(untitled) (Applied Biological Research, 2023)
Children are most exposed to under nourishment because of high dietary requirements for their growth and development. The present study was aimed to determine the prevalence of underweight children in age group of 6-59monthsinMeisso district, Oromia (Ethiopia) and identify the associated factors responsible for it. A community based cross sectional study was conducted on 296 children. The data was collected by using a well structured pretested questionnaire. Anthropometric measurements of children were taken to assess their nutritional status. Generalized ordered logit model, proportional odds model and partial proportional odds model were compared and finally the partial proportional odds model was taken as the best model for current study to identify the factors associated with the nutritional status of children. The study showed that underweight was a serious problem in Miesso district with the prevalence of severe underweight as 24.0% and those of mild underweight as 26.7%. The predictors significantly related to the child nutritional status were sex, age, household’s food security status and the toilet using status of family, since the child malnutrition in the district was very highly prevalent continuous nutrition supervision and special attention to severely malnourished children is necessary to overcome malnutrition problem.